Estimated differences in economic and environmental performance of dairy herds across the UK - Bell, M.J.; Wilson, P. (Association of Applied Biologists, 2017)
Production data were obtained from about half a million milk recorded dairy cows and the Farm Business Surveys for England, Scotland, Wales and Northern Ireland. This study modelled the average herd in each region between the years 2010 to 2015 and assessed the impact of a single unit change on the economic value and greenhouse gas emissions intensity (expressed as carbon dioxide equivalents per kg milk solids) for selected production, health and fertility traits associated with dairy cows. The results of this study show that there are differences in the average production of dairy herds across regions of the UK; however, only slight differences in calculated economic values and emissions intensity values associated with biological traits were found. Recognising the regional and potential genotype x environment differences associated with milk production, and providing a methodology to assess these differences at the farm level, would help improve the resilience and efficiency of milk production in the future.